Leadership practices of high performing principals in selected Malaysian secondary schools: applying normative leadership models - Norwawi, Shaharizal (2018)
Global research suggests that successful school principals are those who apply a judicious mix of instructional, distributed and transformational models of leadership. These approaches are explicitly advocated in the Malaysia Education Blueprint (MEB), the government’s main education reform document that was launched in 2013. The MEB sets out an ambitious plan for all schools to have high performing principals, and high performance is associated with these three models rather than the administrative leadership which is more common in Malaysian schools. The MEB suggests that the aspiration of placing high performing leaders in all schools can be achieved by improving and refining the selection process for new principals, and by requiring them to acquire the National Professional Qualification for Educational Leaders (NPQEL). The MEB also places a strong emphasis on instructional leadership as one of the more effective leadership approaches, which current and future principals should adopt. This thesis presents the findings from a mixed methods study designed to examine the leadership features and practices of principals deemed to be high performing, serving in selected schools in Malaysia. These principals are deemed high performing because they are recipients of two government awards, the Excellent Principals award and the New Deals award. The study examines the extent to which instructional, transformational and distributed leadership are practiced by the principals, drawing on the following data sources: interviews with three senior policymakers; documentary analysis of relevant policies and circulars and questionnaires filled in by 20 ‘high performing’ principals and their teachers. The data is further supplemented with interviews with six out the 20 high performing principals and their respective senior leadership team member and teachers. The findings suggest that principals who are deemed high performing in the selected Malaysian schools enact instructional leadership modestly compared to distributed leadership and transformational leadership. A tentative framework of core leadership practices enacted by principals who are deemed high performing, derived from the findings of this study, is presented at the end of this study.